Clinical Isolates of Mycobacterium tuberculosis Differ in Their Ability to Induce Respiratory Burst and Apoptosis in Neutrophils as a Possible Mechanism of Immune Escape - María M. Romero; Luciana Balboa; Juan I. Basile; Beatriz López; Viviana Ritacco; Silvia S. de la Barrera; María C. Sasiain; Lucía Barrera; Mercedes Alemán (Clinical and Developmental Immunology)
Tuberculosis pathogenesis was earlier thought to be mainly related to the host but now it appears to be clear that bacterial factors are also involved. Genetic variability of Mycobacterium tuberculosis (Mtb) could be slight but it may lead to sharp phenotypic differences. We have previously reported that nonopsonized Mtb H37Rv induce apoptosis of polymorphonuclear neutrophils (PMNs) by a mechanism that involves the p38 pathway. Here we evaluated the capability to induce PMN apoptosis of two prevalent Mtb lineages in Argentina, the Latin America and Mediterranean (LAM), and Haarlem, using the H37Rv as a reference strain. Results showed that LAM strains strongly induced apoptosis of PMN which correlated with the induction of reactive oxygen species (ROS) production and p38 activation. Interestingly, the highly prosperous multidrug-resistant M strain, belonging to the Haarlem lineage, lacked the ability to activate and to induce PMN apoptosis as a consequence of (1) a weak ROS production and (2) the contribution of antiapoptotic mechanisms mediated at least by ERK. Although with less skill, M is able to enter the PMN so that phenotypic differences could lead PMN to be a reservoir allowing some pathogens to prevail and persist over other strains in the community.